Altered RyR2 regulation by the calmodulin F90L mutation associated with idiopathic ventricular fibrillation and early sudden cardiac death. Issue 17 (15th July 2014) - Nomikos, Michail; Thanassoulas, Angelos; Beck, Konrad; Vassilakopoulou, Vyronia; Hu, Handan; Calver, Brian L.; Theodoridou, Maria; Kashir, Junaid; Blayney, Lynda; Livaniou, Evangelia; Rizkallah, Pierre; Nounesis, George; et al.
Abstract : Calmodulin (CaM) association with the cardiac muscle ryanodine receptor (RyR2) regulates excitation–contraction coupling. Defective CaM–RyR2 interaction is associated with heart failure. A novel CaM mutation (CaM F90L ) was recently identified in a family with idiopathic ventricular fibrillation (IVF) and early onset sudden cardiac death. We report the first biochemical characterization of CaM F90L . F90L confers a deleterious effect on protein stability. Ca 2+ ‐binding studies reveal reduced Ca 2+ ‐binding affinity and a loss of co‐operativity. Moreover, CaM F90L displays reduced RyR2 interaction and defective modulation of [ 3 H]ryanodine binding. Hence, dysregulation of RyR2‐mediated Ca 2+ release via aberrant CaM F90L –RyR2 interaction is a potential mechanism that underlies familial IVF. Abstract : A calmodulin mutation (CaM F90L ) linked to sudden cardiac death was characterized. CaM F90L has reduced protein stability, Ca 2+ binding affinity and co‐operativity. The defective interaction of CaM F90L with RyR2 may lead to sudden cardiac death.